Dexmedetomidine sedation combined with caudal anesthesia for lower abdominal and extremity surgery in ex‐preterm and full‐term infants. Issue 6 (2nd March 2017) - Waurick, Katrin; Sauerland, Cristina; Goeters, Christiane
Summary: Background: Awake caudal anesthesia is a potentially attractive option, because the administration of general anesthesia is associated with a high rate of respiratory complications and hemodynamic disturbances and potential neurotoxic effects. To facilitate the caudal puncture and subsequent surgical intervention, additional sedatives are commonly administered. Aim: We aimed to establish a new, safe, and effective anesthetic procedure for very young children with comorbidities. Methods: We retrospectively analyzed 23 children who underwent lower abdominal or lower extremity surgery with dexmedetomidine sedation and caudal anesthesia from January 2015 to August 2015. Dexmedetomidine was initiated with a total bolus infusion of 0.7–1.1 μg·kg −1 followed by a continuous infusion of 1 μg·kg −1 ·h −1 . Bupivacaine (2.5 mg·kg −1 ) was supplemented with 5–10 μg·kg −1 epinephrine to strengthen and prolong motor block. According to maturity at birth, two groups were defined: ex‐preterm and full‐term infants. Results: There were 12 ex‐preterm and 10 full‐term infants available for analysis. The median postmenstrual age was 44 (38–52) weeks in ex‐preterm and 46.5 (40–72) weeks in full‐term infants. Without any additional intervention, surgery was successfully accomplished in 82% of all cases. While respiratory complications were not a problem, hemodynamic disturbances commonly occurred. Maximum decreases in heart rate (HR) of 30% were accompanied by maximum decreases in mean arterial pressure (MAP) of 38%. No infant had a heart rate below 100 bpm. MAP declined in one ex‐preterm infant to a minimum value of 32 mmHg. Conclusion: Caudal anesthesia combined with dexmedetomidine sedation is an effective anesthetic technique for lower abdominal and extremity surgery in ex‐preterm and full‐term infants with severe comorbidities. Abstract :